A Monte Carlo Investigation of Some Tests for Stochastic Dominance - TSE, Yiu Kuen (Institutional Knowledge at Singapore Management University, 2000)
This paper compares the performance of several tests for stochastic dominance up to order three using Monte Carlo methods. The tests considered are the Davidson and Duclos (2000) test, the Anderson test (1996) and the Kaur, Rao and Singh (1994) test. We ﬁnd that the Davidson-Duclos test appears to be the best. The Kaur-Rao-Singh test is overly conservative and does not compare favorably against the Davidson-Duclos and Anderson tests in terms of power.